Pengaruh Product Innovation, Content Marketing Dan Brand Awareness Terhadap Purchase Intention (Studi Pada Consumer Delscakery Di Blok M) - Mutiara, Zahwa; Elizabeth Elizabeth (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The growth of the culinary industry in Indonesia has intensified competition in creating purchase intention. Purchase intention refers to a consumer’s desire to purchase a product or service after undergoing an evaluation and consideration process. In the culinary industry, Product Innovation and Content Marketing in the digital era have become key factors influencing purchase intention. Delscakery faces competitive pressure from Fudgy Bro and Cakeexpress, which are also striving to increase their purchase intention. This study aims to examine the partial effects of Product Innovation, Content Marketing, and Brand Awareness on Purchase Intention among consumers Delscakery in Blok M. This type of quantitative research. The technique of determining the population uses non-probability sampling. The population in this study is unknown. The sample used in this study was 97 respondents, using the accidental sampling method and using the Lemeshow formula. In this study, data were analyzed using the SPSS version 26 program and Microsoft Excel 2024. The results show that Product Innovation and Content Marketing have a significant partial influence on Purchase Intention, whereas Brand Awareness does not have a effect on Purchase Intention.